Study of Flexural Properties between Domestic Glass Fibers Reinforced Polymethylmethacrylate and Dental Glass Fibers Reinforced Polymethylmethacrylate - Angkasith, Pattarika; Kostagianni, Aikaterini; Sastraruji, Thanapat; Chiajareenont, Pisaisit; Chairote, Kasaree; Mandapitak, Palida (Chiang Mai Dental Journal, 2021)
The aim of this study was to examine the flexural properties of PMMA reinforced with domestic glass fibers compared to PMMA reinforced with dental glass fibers. Thirty-two PMMA bar specimens in the size of 10x64x3.2 mm3 (ISO 20795-1) were divided equally into 4 groups (eight specimens for each) according to the types of fibers: 1) no fibers 2) dental fibers 3) silane impregnated domestic glass fibers 4) non-silane impregnated domestic glass fibers. All specimens were subjected to 2,000 cycles of thermocycling. Flexural strength was determined using a three-point loading test set up at a crosshead speed of 5 mm/min by Universal Testing Machine Model 5566. Scanning electron microscopy was used to examine the microstructure of the cracked surface at 200X and 1000X. The results were analyzed by One-way ANOVA and Tukey HSD (α=0.05). Results: The silane impregnated domestic glass fibers demonstrated the highest flexural strength compared to the others while the non-impregnated domestic glass fibers had the lowest flexural strength. CONCLUSION Reinforcing PMMA with silane impregnated domestic glass fibers could improve its flexural strength. Keywords: Flexural Properties, Glass Fibers, Polymethylmethacrylate, Silane Coupling Agent